Calcitonin gene-related peptide is a potential autoantigen for CD4 T cells in type 1 diabetes - Li, Wei; Li, Ronghui; Wang, Yang; Zhang, Yan; Tomar, Munendra S.; Dai, Shaodong (Frontiers in Immunology, 2022)
The calcitonin-gene related peptide (CGRP) is a 37-amino acid neuropeptide with critical roles in the development of peripheral sensitization and pain. One of the CGRP family peptides, Islet amyloid polypeptide (IAPP), is an important autoantigen in type 1 diabetes. Due to the high structural and chemical similarity between CGRP and IAPP, we expected that the CGRP peptide could be recognized by IAPP-specific CD4 T cells. However, there was no cross-reactivity between the CGRP peptide and the diabetogenic IAPP-reactive T cells. A set of CGRP-specific CD4 T cells was isolated from non-obese diabetic (NOD) mice. The T cell receptor (TCR) variable regions of both α and β chains were highly skewed towards TRAV13 and TRBV13 respectively. The clonal expansion of T cells suggested that the presence of activated T cells responded to CGRP stimulation. None of the CGRP-specific CD4 T cells were able to be activated by the IAPP peptide. This established that CGRP-reactive CD4 T cells are a unique type of autoantigen-specific T cells in NOD mice. Using IAg7-CGRP tetramers, we found that CGRP-specific T cells were present in the pancreas of both prediabetic and diabetic NOD mice. The percentages of CGRP-reactive T cells in the pancreas of NOD mice were correlated to the diabetic progression. We showed that the human CGRP peptide presented by IAg7 elicited strong CGRP-specific T cell responses. These findings suggested that CGRP is a potential autoantigen for CD4 T cells in NOD mice and probably in humans. The CGRP-specific CD4 T cells could be a unique marker for type 1 diabetes. Given the ubiquity of CGRP in nervous systems, it could potentially play an important role in diabetic neuropathy.